PROPOSTA DE UM ÍNDICE DE AVALIAÇÃO DA SATISFAÇÃO DE USUÁRIOS DO TRANSPORTE PÚBLICO POR MEIO DA ADAPTAÇÃO DO CUSTOMER SATISFACTION SCORE (CSAT) (REMUNOM, 2024)
This article presents a proposal for a public transport evaluation index through an adaptation of the CSAT (Customer Satisfaction Score) metric, seeking to understand the satisfaction of providing this service in the view of its users. A bibliographic survey was carried out on the main quality indicators of public transport linked to user satisfaction, identifying aspects that would compose the calculation of the proposed index. Based on the adaptation of transport engineering quality indexes through the application of the CSAT metric, a method for evaluating the satisfaction of public transport users was developed. For this, a case study was carried out with bus passengers in São Carlos city. The method made it possible to categorize the degree of relevance of the main aspects that make up the public transport system, in addition to the perception of satisfaction for the users who participated in the research. Crossing those informations resulted in a final satisfaction index of São Carlos’ public urban transportation. The final result categorized the São Carlos’ public transportation customers’ satisfaction as “low unsatisfied”.